THE PROTECTIVE PATHS IN THE INFORMATION SOCIETY: (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The analysis of this study will be made with the focus on the reflexes of the Information Society in the context of personal data. Because, with the widespread use of an almost global way of computers and other devices connected to the web (Internet of things), people obtained accessibility to a myriad range of informational content, services and tools for the acquisition of consumer goods. However, at the same time, individuals were exposed in an environment which, in most cases, does not provide a list of mechanisms to protect them in the face of the threats external digital (other users) and internal (deleterious programs to the internet). Thus, some countries began to adopt various forms of protection of personal data in the worldwide network of computers, among them: self-regulation, the traditional regulation and non-regulation. Some States drew up legal standards for such protection (judicialization), while others are guide by use of ethics in internet (internethic). In this way, through researches about the doctrine, sites and academic papers related to the theme, comes to the conclusion that in Brazil there is a need for a protective system of private information on the internet. For these reasons, this article, simply, aims to point to some protective paths for users of digital environments.